2012
DOI: 10.1177/1066896912457204
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Effectiveness of GEWF Solution in the Identification of Lymph Nodes in Specimens of Colorectal Carcinoma

Abstract: Lymph node status is pivotal in the staging process of cancer. With regards to colorectal cancer, lymph node retrieval is always laborious. Sometimes, it is also a challenge to recover a minimum of 12 lymph nodes from the pericolorectal tissue. Among many proposed adjunctive solutions, GEWF solution (glacial acetic acid, ethanol, distilled water, and formaldehyde) has been introduced recently and suggested to be superior. To further evaluate its efficiency, the pericolorectal tissue, which has been reexamined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Secondary dissection resulted in the detection of more lymph nodes, in keeping with previous studies 9 16 37–43 45 46. We found that GEWF was not superior to formalin fixation in this respect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Secondary dissection resulted in the detection of more lymph nodes, in keeping with previous studies 9 16 37–43 45 46. We found that GEWF was not superior to formalin fixation in this respect.…”
Section: Discussionsupporting
confidence: 92%
“…Studies using GEWF, a mixture of glacial acetic acid, ethanol, water and formalin, suggested that its use will identify an increased number of lymph nodes,9 37–43 45–46 and that this may lead to stage migration from node negative to positive 19 27 29 34 42 43. GEWF has been shown to facilitate identification of smaller lymph nodes,9 38 41 42 46 which may be especially useful for cases where neoadjuvant therapy has been given, as there is often a paucity of lymph nodes that are also smaller in size 8…”
Section: Introductionmentioning
confidence: 99%
“…3 18 19 22 25 36 39 40 42 44 Some of the more recent studies using GEWF have assessed and attributed statistical significance to this 36 39 40 42. Brown et al 27 found that 83% of additional lymph nodes were ≤2 mm in size.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As a result of this, only one study in the last 10 years has included xylene 27. In contrast, there have been a number of recent studies assessing the use of GEWF, which is seen as a better lymph node revealing solution than its predecessors because it is safe, cheap, easy to prepare and handle,3 35 36 38–41 43 44 odourless, can be used with standard ventilation, and has no adverse effect on routine special stains or immunohistochemistry 36…”
Section: Challenges In Study Designmentioning
confidence: 99%
“…It involves using a mixture of glacial acetic acid, ethanol, water and formaldehyde (GEWF). The number of studies is fairly small and although a significant increase in lymph node number has been reported, the absolute yield is not reported consistently across studies [65,66,67,68,69]. The use of GEWF solution for 12-24 h increases the harvest from 9 to 15 lymph nodes for colon cancer and from 10 to 16 for rectal cancer without increasing the percentage of stage III cancer [66].…”
Section: Resultsmentioning
confidence: 99%